Development of Humor Learning: Learning Strategy Increasing Learning Result of Student Class IV Primary School - Ritonga, Rudi; Marhadi, Hendri; Antosa, Zariul; Mulyani, Eva Astuti (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
Learning by using learning strategies that have been adapted to thecharacteristics of teachers and students, of course have more value.This study aims to develop a humor based learning strategy that creates active learning, creative and fun, is the goal of the research undertaken. This research is RnD (Research and Development ) which use 4- D development model (Define, Design, Develope, and Disseminate ). However, this stage of research has not yet done the dissemination of learning device development outcomes. The research instruments are questionnaires of teacher and student needs, observation sheet, interview, validation sheet, teacher and student response questionnaire, and science learning result test . Product from research in the form of Learning Implementation Plan (RPP), learning module, and Student Worksheet (LKS). The result of the research shows that 1) learning tools that refer to humor based learning strategy include learning implementation plan, learning strategy, and LKS according to expert judgment in general are included in good category, 2) student and teacher response to learning based on humor based learning strategy generally show senan g to the learning process using anew strategy of learning based on humor and has never been used before, and tersikrik with performance LKS learning, and 3) Strategy learning based humor is effectively used in distance learning in space. From the results of these studies, it can be concluded that the development of learning strategies based on humor, practical, and effective.